An Attempt Toward the Global Screening of Soybean Viruses Using EDNA-MiFi-Based Electronic Probes - Ribeiro-Junior, Marcos R. [UNESP]; Espindola, Andres; Nascimento, Daniele M.; da Silva, Felipe Barreto [UNESP]; Krause-Sakate, Renate [UNESP]; Ochoa-Corona, Francisco M. (Scientific Societies, 2025)
Soybean ( Glycine max) is a globally significant crop renowned for its oilseed and protein content. Brazil and the United States are the leading producers worldwide. However, viral diseases are a persistent threat to the soybean industry, resulting in annual yield losses. Accurate and rapid diagnosis is essential for effective disease management. This study presents the application of Electronic-probe Diagnostic Nucleic-acid Analysis and Microbe Finder (EDNA-MiFi), a web-based software designed for rapid identification of predetermined pathogen species in high-throughput sequencing (HTS) datasets. MiFi uses curated electronic probes (e-probes) specific to target sequences, enabling screening of raw, unassembled HTS data. E-probes (20 to 60 nt) for 46 known soybean-infecting viruses were designed using MiProbe, a MiFi platform component. E-probe curation and validation involved BLASTn analyses and the creation of mock HTS data consisting of positive controls of reference virus and host genome sequences. The in silico analysis confirmed the efficacy of the e-probes in detecting all 46 viruses in the metatranscriptomic soybean data. The in vitro analysis was conducted with Illumina HTS data from soybean collected in Brazil. Results showed infections with nine virus species, which were further validated through PCR, RT-PCR, and mapping of reads to virus reference genomes. This study demonstrates that MiFi enables rapid (less than an hour) detection of targeted virus sequences in raw HTS outputs based on the screening of all currently reported soybean-infecting viruses. The curated e-probes specific to soybean viruses are accessible for diagnostic purposes via MiDetect, another component of the MiFi platform. [Formula: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .